Search for pair production of vector-like quarks in the bW(b)over-barW channel from proton-proton collisions at root s=13TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Ero,J; Flechl,M; Friedl,M; et al. (PHYSICS LETTERS B, 2018)
A search is presented for the production of vector-like quark pairs, or , with electric charge of 2/3 (T) or (Y), in proton–proton collisions at . The data were collected by the CMS experiment at the LHC in 2016 and correspond to an integrated luminosity of . The T and Y quarks are assumed to decay exclusively to a W boson and a b quark. The search is based on events with a single isolated electron or muon, large missing transverse momentum, and at least four jets with large transverse momenta. In the search, a kinematic reconstruction of the final state observables is performed, which would permit a signal to be detected as a narrow mass peak (≈7% resolution). The observed number of events is consistent with the standard model prediction. Assuming strong pair production of the vector-like quarks and a 100% branching fraction to , a lower limit of 1295 GeV at 95% confidence level is set on the T and Y quark masses.